The Use of Levonorgestrel Releasing Intrauterine System at Ahmadu Bello University Teaching Hospital, Zaria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:The intrauterine system (IUS) is an intrauterine device which releases levonorgestrel (LNG). It is used in preventing pregnancy for up to 5 years as well as to treat heavy menstrual bleeding. Data documenting the use of IUS is very limited in our setting.Objective:To review the use of the LNG IUS and the reasons for its use.Materials and Methods:In this study, we reviewed records of all clients who attended the reproductive health clinic of the Ahmadu Bello University Teaching Hospital, Zaria and selected an intrauterine device as a method of contraception and or therapeutic option. The study was conducted from January 2007 to December 2013. Data was analysed using the Statistical Package for the Social Sciences (SPSS) version 20.Results:A total of 1104 women opted for an IUD as a method for contraception, of which 68 (6.1%) women used LNG IUS. The mean age of the women was 31.9 years ± 6.8 years. Over half (54.5%) had between 2 and 4 children. There were only 6 (11.8%) women who used the IUS for reasons other than contraception during the study period, majority had the device inserted for contraception. Side-effect was the major reason for discontinuation (29.4%) followed by the desire to have a baby (27.9%). The most common side-effect was irregular vaginal bleeding (23.5%).Conclusion:The uptake of LNG IUS (Mirena®) for contraception or therapy is very low in our setting. There is a need to educate both the healthcare providers and clients regarding the contraceptive and non-contraceptive benefits of Merina.